Determination of the Coefficient of Internal Friction of Ice - Shimko,G. N. (1970)
The dependence of the dielectric permeability of ice on temperature leads to the assumption that the polar radicals in the crystal lattice can vibrate. The dielectric permeability also depends on the frequency of the applied voltage and is subject to the laws that apply to dipole liquids. The static dielectric permeability for ice is given, the optical value of the dielectric permeability is given. If the time of relaxation is known, the coefficient of internal friction can be calculated. Using the method of approximations, a given empirical formula is obtained, where T is the absolute temperature. Knowing the coefficient of internal friction, the dielectric parameters of ice can be determined within a wide frequency range and at any temperature. (Author) Edited machine trans. of mono. Nauchnye Trudy Vysshikh Uchebnykh Zavedenii Litovskoi SSR. Elektrotekhnika i Avtomatika, IV, n.p., 1968 (Scientific Transactions of Higher Eductional Institutions of the Lithuanian SSR. Electrical Engineering and Automation, IV, n.p., 1968), n.p., 1969 n4 p193-198, by Lee D. Thompson.